In situ observation of the effect of the twin boundary orientation on the mechanical properties of single crystalline Ni. (July 2022) - An, Zibing; Li, Zhipeng; Zhang, Jianfei; Zhang, Ze; Mao, Shengcheng; Han, Xiaodong
Graphical abstract: Highlights: Ni sample with different twin boundary orientation was created by FIB, and their effect on mechanical properties was revealed by in situ TEM. The sample with a twin boundary vertical to the tensile direction achieved high tensile uniform elongation (120%). Dislocation interaction before reaching the perpendicular CTB contribute to cross-slip and in situ formation of dislocation jogs. Abstract: The construction of twin boundaries (TBs) in materials is a remarkable way of promoting their strength and ductility. However, the effects of TB orientation on the mechanical properties have not been reported experimentally so far. Using a state-of-the-art in situ tensile stage equipped in a transmission electron microscope, uniaxial tensile tests were performed on three single-crystalline Ni samples with TB parallel and perpendicular to the tensile direction and no TB. The results showed that the uniform tensile elongation strongly depends on TB, 120% for the perpendicular TB sample, 99% for the parallel TB sample, and only 55% for the no TB sample. In addition, dislocation interaction before reaching the perpendicular CTB contribute to cross-slip and dynamic formation of dislocation jogs, thereby improving strain hardening and resulting in a large uniform tensile elongation.